2020
DOI: 10.1002/uog.20846
|View full text |Cite
|
Sign up to set email alerts
|

High risk of long‐term neurodevelopmental impairment in donor twins with spontaneous twin anemia–polycythemia sequence

Abstract: CONTRIBUTIONWhat are the novel findings of this work? Donor twins of pregnancies complicated by spontaneous twin anemia-polycythemia sequence (TAPS) have four-fold higher odds of neurodevelopmental impairment compared with their recipient cotwins, are at increased risk of cognitive delay and have a high rate of deafness. What are the clinical implications of this work?Based on our findings, we strongly advise that routine long-term follow-up, including testing for hearing loss, should be an essential part of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
2
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 27 publications
0
36
2
4
Order By: Relevance
“…However, laser surgery was associated with a high diagnosis-to-birth interval, especially in comparison to treatment with IUT (± PET). As prematurity has a profound impact on short-and long-term health in TAPS twins, prolongation of pregnancy is of the utmost importance to improve outcome 6,7,10,11 . Notably, a comparable prolongation of pregnancy was achieved with selective feticide and expectant management.…”
Section: Perinatal Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…However, laser surgery was associated with a high diagnosis-to-birth interval, especially in comparison to treatment with IUT (± PET). As prematurity has a profound impact on short-and long-term health in TAPS twins, prolongation of pregnancy is of the utmost importance to improve outcome 6,7,10,11 . Notably, a comparable prolongation of pregnancy was achieved with selective feticide and expectant management.…”
Section: Perinatal Outcomementioning
confidence: 99%
“…Moreover, long-term outcome was not investigated in this study. Previous studies have shown that the detrimental effects of TAPS are not limited to the perinatal period, but also manifest later in life 6,7 . Therefore, the true effect of management for TAPS can only be properly investigated when TAPS cases are randomized between treatment groups, when stratification for risk factors is applied, and when long-term consequences are taken into account.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a reported incidence of spontaneous onset in 3-5% of MCDA twins, and 2-16% in cases after laser photocoagulation for TTTS [2][3][4][5][6]. It is known to be associated with increased perinatal morbidity and mortality [1], and neurodevelopmental impairment [7,8]. The optimal management of TAPS remains uncertain, but strategies varying from fetoscopic laser therapy, intrauterine transfusion with or without partial exchange transfusion, selective reduction, early delivery, to expectant management have been described [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…▪ MC-Zwillinge mit TAPS haben ein erhöhtes Risiko für eine neurologische Entwicklungsverzögerung. ▪ Es wird eine zerebrale Bildgebung im dritten Trimenon sowie eine entwicklungsneurologische Untersuchung im Alter von 2 Jahren empfohlen[52,53] (▶ Tab. 2).…”
unclassified